Impact of Globalisation on Economic Growth in Romania: An Empirical Analysis of Its Economic, Social and Political Dimensions - Neagu, Olimpia; Dima, Stela (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2017)
The paper analyses the link between globalisation and economic growth in Romania for a time span of 24 years. Data from World Bank were used in an econometrical model in order to highlight the impact of globalisation, expressed by the KOF globalisation index and its components (economic, social and political globalisation indices) on economic growth rate. A statistical strong and positive link is found between GDP per capita dynamics and overall globalisation index as well as between GDP growth rate and economic and political globalisation, except the social dimension of globalisation which has a negative impact on economic growth in Romania for the time span 1990-2013.